Changes in Global Power Relations, Geopolitical Complexity and Nepal's National Security Challenges - K.C., Khadga (Unity Journal, 2023)
There are clear signs that the balance of power in the globe is shifting. The USA, an established superpower, and China, a developing superpower, are vying for the world's attention. Eventually, Russia is showing strength to establish herself as one of the other axis powers to transform the global order from unipolar to multipolar. India, Nepal's immediate neighbor with an open border and decades-old, strong bilateral links, is also evolving into a regional power, or at the very least, is on track to appear as the world's second-largest economy in near future. In this juncture, Nepal is more of security significance to China, India, and the US due to its geostrategic location. Nepal, which is constrained by a number of treaties with India, has already declared its support for both the US Millennium Challenge Corporation and China's Belt and Road Initiative. The New World Order has seen a new regional security climate in South Asia and growing polarization leading to large power rivalry forming a China-India plus the US . Additionally, attempts are being made to strengthen the security ties between the US and Nepal through the State Partnership Program (SPP) and with China through the Chinese Global Security Initiative (GSI), both of which may pose serious challenges to Nepal's national security. Thus, Nepal must maintain strict nonalignment foreign policy, increase the use of soft powers, and take a proactive, impartial, and balanced attitude in its diplomatic operations in order to face the expanding national security challenges resulted from geopolitical complexity. Also, Nepal needs to maintain strategic balance among the great powers, promoting the value of green energy and nurturing soft power. For Nepal, accomplishments of such goals and objectives through the preservation of the Himalayas, promoting Nepal's rich cultural heritage of the Buddha and accelerating mililtary diplomacy in the UNPKO have been indispensable. Nepal's foreign and national security policy should be both inside and outward looking, fostering her regional and the multilateral engagements in SAARC, BIMSTEC, Shanghai Cooperation, and the United Nations.